A BRIEF REVIEW ON PHARMACOLOGICAL BENEFITS OF VERBASCUM THAPSUS L - Riya Vaghela; Nadim Chhipa; Pragnesh Patani (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Verbascum Thapsus L., often known as common mullein, is a medicinal plant that is easily located along roadsides, in meadows, and on grazing grounds. It has been used to treat a variety of conditions, including asthma, inflammatory disorders, lung issues, diarrhea, and migraine, headaches. Common mullein has been used medicinally since ancient times, but in recent years, its popularity has grown economically. A growing body of research investigations has been conducted in support of the use of common mullein extracts in folk medicine in recent times. Detailed review and its pharmacological actions are highlighted in this article which can be one of the promising herbs for the treatment of variety of disorders related to inflammatory and allergic conditions.